2000
DOI: 10.1074/jbc.m006016200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α-induced Expression of 20α-Hydroxysteroid Dehydrogenase Involves the Transcription Factor NUR77

Abstract: Prostaglandin F 2 ␣ (PGF 2 ␣) binding to its receptor on the rat corpus luteum triggers various signal transduction pathways that lead to the activation of a steroidogenic enzyme, 20␣-hydroxysteroid dehydrogenase (20␣-HSD), which in turn catabolizes progesterone. The molecular mechanism underlying PGF 2 ␣-induced 20␣-HSD enzyme activity has not yet been explored. In this report we show, using mice lacking PGF 2 ␣ receptor and pregnant rats, that PGF 2 ␣ is responsible for the rapid and massive expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
96
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 62 publications
5
96
3
Order By: Relevance
“…However, most ovarian studies remained largely at the level of the corpus luteum. Early investigations on the luteolytic effects of PGF 2 showed that 20 -HSD activity is induced 150-fold in the rat ovary (Strauss & Stambaugh 1974), this being consistent with more recent findings that demonstrate that rat 20 -HSD (AKR1C8) is induced by PGF 2 (Stocco et al 2000). The transcription factor Nur77 was shown to play a key role in the PGF 2 -dependent induction of 20 -HSD (AKR1C8) in rat luteal cells (Stocco et al 2000).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, most ovarian studies remained largely at the level of the corpus luteum. Early investigations on the luteolytic effects of PGF 2 showed that 20 -HSD activity is induced 150-fold in the rat ovary (Strauss & Stambaugh 1974), this being consistent with more recent findings that demonstrate that rat 20 -HSD (AKR1C8) is induced by PGF 2 (Stocco et al 2000). The transcription factor Nur77 was shown to play a key role in the PGF 2 -dependent induction of 20 -HSD (AKR1C8) in rat luteal cells (Stocco et al 2000).…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, because of confusion regarding nomenclature, difficulties lie in identifying precisely which AKR was being studied in previous publications. Many reports addressed the regulation of AKRs speculated to have 20 -HSD activity in various tissues, including the ovary (Strauss & Stambaugh 1974, Lacy et al 1993, Albarracin et al 1994, Stocco et al 2000, Pelletier et al 2003. However, most ovarian studies remained largely at the level of the corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of testicular steroidogenesis in Leydig cells is mediated through multiple signaling pathways and nuclear factors that generate both positive and negative effects on steroidogenic response (8,(37)(38)(39). The cAMP-dependent protein kinase A signaling pathway is a major pathway for testicular steroidogenesis, which is primarily controlled by the pituitary gonadotropin LH in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…LH/cAMP stimulates steroidogenesis by increasing the expression of steroidogenic enzyme genes (1). Recently, it was demonstrated that LH induces Nur77 gene expression in Leydig cells (2), and Nur77 in turn regulates the expression of steroidogenic enzyme genes (3-6) such as cytochrome P450 protein 17, the steroid 21-hydroxylase, and 20-␣-hydroxysteroid dehydrogenase (7,8), suggesting an important role for Nur77 in testicular steroidogenesis.…”
mentioning
confidence: 99%